PENERAPAN DIVERSI PADA PELAKU TINDAK PIDANA LALU LINTAS YANG DILAKUKAN OLEH ANAK MENGAKIBATKAN HILANGNYA NYAWA ORANG LAIN (Studi Kasus Putusan Pengadilan Negeri Jember Nomor 7/Pid.Sus-Anak/2018/PN.Jmr) - GUSTANA S, SAKTI RANGGA (Dinamika Hukum, 2019)
The purpose of this research is to examine the application of the version of traffic crimes resulting from the loss of the lives of other people at Jember District Court Decision No. 7/Pid. Sus-Child/2018/PN.Jmr. Reviewing the judgment of judges in the Impose sanctions on children perpetrators of criminal traffic that resulted in the loss of other people's lives on the decision of the District Court of Jember No. 7/Pid. Sus-Child/2018/PN.Jmr. The method of approach in writing is normative juridical. The specification of this research uses analytical descriptive. The data source uses the Skunder data. Data collection techniques using library studies. To analyze the data, researchers use qualitative descriptive analysis methods. The application of a version of the perpetrators of criminal traffic that resulted in another person's death by the son on Jember state Court decision number: 7/Pid. Sus-Child/2018/PN. JMR refers to article 7 paragraph (2) of Law No. 11 of 2012 concerning Child criminal justice system. That the settlement of child criminal cases can be done in a version when the threat of criminal offence is under 7 (seven) years and not a repetition of a criminal offense. District Court Judge Jember in dropping actions against children in conflict with the law also refers to the provisions of Article 69 paragraph (2) of Law No. 11 of 2012 on the Child criminal justice system stating that: a conflicted child With a law that is not yet 14 (fourteen) years old can only be subject to a return to parents. The sanction of action to the defendant is based on the defendant is not yet 14 years old and aims to rescue and release the defendant from the crime stigma by returning the parents. Consideration of judges in the criminal subpoena against the perpetrators of criminal traffic that resulted in others passed away by the son on the decision of the District Court of Jember No: 7/Pid. Sus-Child/2018/PN. JMR is based on the witness description, The tools of evidence in the form of letters, expert information, instructions, information of defendants, prosecution indictment and the results of public research by public advisers from the BAPAS. In addition to the consideration of the evidence tool, the judge also considers that the defendant Anak is still school and underage, and the child does not know and understand the traffic signs, without wearing a helmet and without having SIM C which in terms of children's age is also not It's time to drive a motorcycle so the child doesn't understand how much speed is allowed when riding a motorcycle on a highway. Keywords: Child criminal justice system, traffic criminal act.